IDᾹRAT BARNᾹMAJ AL LUGHAH FĪ INTᾹJI AL AJYᾹL AL MUTAFAWWIQAH BI ALLUGHAH AL‘ARABIYYAT LADA AL MUASSASATI AL NᾹTHIQ AL ‘ᾹLAMI AL ‘ARABI - Syahrayni, Nurul; Yanti, Sri Afrida; Kholid, Nur (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
Mastering the Arabic language is the dream of every learner of the Arabic language in Indonesia. The objectives of this research consist of two goals, the first is to find out how to manage the language program in producing outstanding generations in the Arabic language at the Arab International Speaking Foundation, and the second is to know the reflection of the language program on the formation of outstanding generations in the Arabic language at the Arab International Speaking Foundation. The researchers use descriptive qualitative research. It uses the data analysis technique of Milles and Hubermen with four stages data reduction, data presentation, data condensation, and inference. Data reduction is obtained in the field by choosing things related to language programs such as study hours, weekly activities, monthly activities, welcoming new students on the 10th or 25th of each month, data presentation is the data taken from the data collected and then arranged in a narrative paragraph so that it becomes Structured data Data condensation is a process of selection Focusing on, simplifying, summarizing, and changing field notes, interview transcripts, documents, or data in the field While inference is concluding the data collected to select data worth publishing. The results of this research indicate that the management of the language program in the production of outstanding generations in the Arabic language at the International Arabic Speaking Foundation includes four essential points: planning, organization, implementation, and evaluation.